MORAL DEVELOPMENT OF A HARD CHILD: FOCUS ON SCHOOL-FAMILY RELATIONSHIP - Trambaiolli De Nadai, Sandra Cristina [UNESP]; Vicentin, Vanessa Fagionatto; Bozza, Thais Leite [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
From a scholar case report, this paper intended to comprehend and analyze school's interventions in the moral development of a hard child, especially relating to school-family. From that case analysis, it was concluded that the child lives at a scholar autocratic environment with no rules thinking, with no concern about student's emotions, which uses expiatory sanctions for educating. It was also concluded that exists a difficulty in establishing a partnership between school and family because conflicts were delegated from the first one to the second one.
Keywords: Interpersonal conflicts; Moral development; School-family partnership